The first record of the genus Dipteranthus (Orchidaceae) in the Guyana, description of a new species - Szlachetko, Dariusz L.; Lipińska, Monika M.; Skorowska, Iwona (Biodiversity: Research and Conservation, 2018)
The orchid genus Dipteranthus, described by Rodrigues in 1882, comprises about 10 species distributed from Venezuela to Bolivia and Brazil. Plants of Dipteranthus are small epiphytes, reaching in total up to 10 cm in length, hence, are easily overlooked in the field. Modern classification of Dipteranthus is still under discussion. During the revision of orchids of the Guianas, we came across some specimens that do not match morphological characters of any previously known Dipteranthus species. Thus, we propose that these specimens represent a new species – Dipteranthus clarkei sp. nov. D. clarkei is the first representative of the genus known from Guyana.